Mesenteric-Portal Vein Resection during Pancreatectomy for Pancreatic Cancer. (1st November 2015) - Beltrame, Valentina; Gruppo, Mario; Pedrazzoli, Sergio; Merigliano, Stefano; Pastorelli, Davide; Sperti, Cosimo
Abstract : The aim of the present study was to determine the outcome of patients undergoing pancreatic resection with (VR+) or without (VR−) mesenteric-portal vein resection for pancreatic carcinoma. Between January 1998 and December 2012, 241 patients with pancreatic cancer underwent pancreatic resection: in 64 patients, surgery included venous resection for macroscopic invasion of mesenteric-portal vein axis. Morbidity and mortality did not differ between the two groups (VR+: 29% and 3%; VR−: 30% and 4.0%, resp.). Radical resection was achieved in 55/64 (78%) in the VR+ group and in 126/177 (71%) in the VR− group. Vascular invasion was histologically proven in 44 (69%) of the VR+ group. Survival curves were not statistically different between the two groups. Mean and median survival time were 26 and 15 months, respectively, in VR− versus 20 and 14 months, respectively, in VR+ group p = 0.52 . In the VR+ group, only histologically proven vascular invasion significantly impacted survival p = 0.02, while, in the VR− group, R0 resection p = 0.001 and tumor's grading p = 0.01 significantly influenced long-term survival. Vascular resection during pancreatectomy can be performed safely, with acceptable morbidity and mortality. Long-term survival was the same, with or without venous resection. Survival was worse for patients with histologically confirmed vascular infiltration.